Analysis of 16S rRNA genes reveals reduced Fusobacterial community diversity when translocating from saliva to GI sites - Richardson, Miles (2020)
Fusobacterium nucleatum is a Gram-negative oral commensal anaerobe which has been increasingly implicated in various gastrointestinal (GI) disorders, including inflammatory bowel disease,appendicitis, GI cancers. The oral cavity harbors a diverse group of Fusobacterium, and it ispostulated that F. nucleatum in the GI tract originate from the mouth. It is not known, however, ifall oral Fusobacterium translocate to the GI sites with equal efficiencies. Therefore, we amplified 16SrRNA genes of F. nucleatum and F. periodonticum, two closely related oral species from matchedsaliva, gastric aspirates, and colon or ileal pouch aspirates of three patients with inflammatorybowel disease (IBD) and three healthy controls, and saliva alone from seven patients with eitheractive IBD or IBD in remission. The 16S rRNA gene amplicons were cloned, and the DNA sequencesdetermined by Sanger sequencing. The results demonstrate that fusobacterial community composition differs more significantly between the oral and GI sites than between different individuals.The oral communities demonstrate the highest level of variation and have the richest pool ofunique sequences, with certain nodes/strains enriched in the GI tract and others diminished duringtranslocation. The gastric and colon/pouch communities exhibit reduced diversity and are moreclosely related, possibly due to selective pressure in the GI tract. This study elucidates selectivetranslocation of oral fusobacteria to the GI tract. Identification of specific transmissible clones willfacilitate risk assessment for developing Fusobacterium-implicated GI disorders.